Utilization of Tasikmadu Starfruit Waste Compost for The Growth and Yield of Purple Eggplant (Solanum melongena L.) In Supporting Sustainable Agriculture - Sumiasih, Inanpi Hidayati; Fauzi, Ahmad Rifqi; Sumarno, Indra (International Journal of Applied Biology, 2024)
Based on the literature study, the demand for eggplant in East Java is increasing, encouraging farmers to increase productivity by using chemical fertilizer. In the long term, this practice could harm the environment. This study was conducted to obtain the right method and dosage of compost made from starfruit waste for the growth and yield of eggplant. The study was designed using a Factorial Randomized Block Design. The first factor was organic fertilizer with 5 levels, namely: Soil + goat manure 1:1, Soil + compost from composter 1:1; Soil + compost from bio-pore1:1; Soil + goat manure + compost from composter 1:1:1, and Soil + goat manure + compost from bio-pore 1:1:1. The second factor was NPK fertilizer with 4 levels, namely: 0 gram/liter, 1 gram/liter; 2 gram/ liter; dan 3 gram/liter. There were three replications for each treatment. The results showed that the best organic fertilizer was a combination of manure and compost, from composter and bio-pore, which had the highest result for plant height, number of leaves, biomass increase, and the number of eggplant fruits. The best concentration of NPK fertilizer for eggplant growth and physiology was 3 grams per liter.